Beraksi (Washing Hand, Care Health, Safe from Infection): Health Education to Increase Knowledge of Personal Hygiene and Handwashing - Yamin, Ahmad; Lukman, Mamat; Mulya, Adelse Prima (Universitas Padjadjaran, 2024)
Health issues such as diarrhea or worm infections are related to personal hygiene and environmental cleanliness. One contributing factor is handwashing habits. Handwashing is a crucial component of personal hygiene because the consequences of not washing hands can lead to health problems related to the digestive system (diarrhea, worm infections, hepatitis, typhoid, etc.). The objective of this health education is to assess its influence on the knowledge of personal hygiene and handwashing practices among elementary school children at SD Mekasari Sayang in Sumedang district. The implementation method of health education involves using video and poster presentations, lectures, discussions, demonstrations, and simulations with 25 first-grade students of SDN Mekarsari conducted directly. Data analysis utilizes pre-post test design with Wilcoxon statistical testing to identify the significance of differences before and after the health education intervention. The results of the activity demonstrate differences in knowledge and handwashing practices before and after health education using film, posters, discussion, simulation, and demonstration methods (p-value < 0.05). The conclusion drawn from this health education is an improvement in students' knowledge and practices after the intervention. It is hoped that students' awareness and habits regarding personal hygiene behavior will increase, thereby preventing various health problems (diseases) that may arise. Keywords: Personal Hygiene, health education, handwashing, elementary school students.